The Effectiveness of Aloe Vera on Relief of Irritation and Nipple Pain in Lactating Women: Systematic Review and Meta-Analysis - Azam Maleki; Samaneh Youseflu (Obstetrics and Gynecology International, 2022)
Background. Aloe vera is one of the herbal products with anti-inflammatory, antioxidant, moisturizing, bactericidal, anti-viral, and anti-fungal effects that were used to relieve pain and irritation. The aim of the current systematic review and meta-analysis is to determine the effect of Aloe vera on the relief of irritation and nipple pain in lactating women. Methods. A search was carried out in four English electronic databases including Scopus, Embase, PubMed, and Web of Science until November 2021. All clinical trials that assessed the effect of Aloe vera on the relief of irritation and nipple pain in lactating women were included. The study’s risk of bias was assessed using the Cochrane risk of bias checklist. Study heterogeneity was determined using the I2 statistic and publication bias using Begg’s and Egger’s tests. Results of the random-effects meta-analysis were presented using standard mean difference (SMD) with 95% confidence intervals (CIs). Data were analyzed using STATA software version 16 MP. Results. In total, 7 articles with 1670 subjects were included in the meta-analysis. Overall, we found a positive impact of Aloe vera on reducing breast pain (pooled SMD= −0.45; CI= −0.83, −0.07, P value <0.02) and irritation (pooled SMD= −0.48; CI= −0.64, −0.32, P value<0.001) in lactating women. There is a high heterogeneity among pain studies (I2= 86%) but was low within irritation studies (I2= 26%). Conclusion. Our result showed that Aloe vera can be considered a choice for relieving breast pain or irritation in lactating women compared with routine care or another treatment. Considering the limited number of studies conducted on this topic and the low sample size, future studies with a larger sample will be required to draw better conclusions.